2019
DOI: 10.1002/jssc.201900281
|View full text |Cite
|
Sign up to set email alerts
|

Molecularly imprinted polymer film grafted from porous silica for efficient enrichment of steroid hormones in water samples

Abstract: Steroid hormones as endocrine disrupting compounds can interfere with the functioning of hormonal systems of organisms and thus affect the health and reproduction of humans and wildlife. Unfortunately, these types of harmful endocrine disrupting compounds have been found in a variety of environmental samples at very low concentrations. Therefore, a simple, fast, and efficient method for enrichment of water samples is needed. A molecularly imprinted solid‐phase extraction combined with high performance liquid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Enrichment of steroid hormones using molecularly imprinted polymer (MIP) films was described by Czarny et al (2019). The authors state that MIP solid‐phase extraction provides advantages over conventional SPE sorbents in efficiency and selectivity.…”
Section: Methodsmentioning
confidence: 99%
“…Enrichment of steroid hormones using molecularly imprinted polymer (MIP) films was described by Czarny et al (2019). The authors state that MIP solid‐phase extraction provides advantages over conventional SPE sorbents in efficiency and selectivity.…”
Section: Methodsmentioning
confidence: 99%
“…The method proved to be suitable for quantification of steroid hormones in water because it had relatively low LODs in the range of 0.0182-0.0898 µg/mL. In addition, high recoveries (79-101%) and low matrix effects (<20%) suggested that the developed MIP-SPE method could be used for selective identification and quantification of the target analytes [91].…”
Section: Water Samplesmentioning
confidence: 99%
“…The method proved to be suitable for quantification of steroid hormones in water because it had relatively low LODs in the range of 0.0182-0.0898 µg/mL. In addition, high recoveries (79-101%) and In another study, the MIP-SPE method was coupled with high-performance liquid chromatography coupled with diode array detection (HPLC-PDA) for selective determination of E1, E2, E3, 17-α-EE2, PRO, and TST in water [91]. The method proved to be suitable for quantification of steroid hormones in water because it had relatively low LODs in the range of 0.0182-0.0898 µg/mL.…”
Section: Water Samplesmentioning
confidence: 99%
“…In addition, the MIP particles synthesized via various surface imprinting techniques, such as surface grafting and coating on substrates, can present fast binding kinetics to target analytes due to the binding sites at/close to the adsorbent surface and consequently also utilized for MISPE [55,56,77–79]. A kind of water compatible ionic‐liquid‐based MIP‐grafted PSD microspheres (Figure 7C) was prepared in water by Zhu et al.…”
Section: Applications Of Molecularly Imprinted Polymer‐based Spe To Rmentioning
confidence: 99%